Associação entre macrossomia ao nascer e nível de atividade física em pré-escolares - Andrade, Acácia Emanuela Souza Pinto (2010)
The genesis of many cardiovascular diseases is obesity. Physical activity is considered a protective factor for obesity. The way the time and intensity in which physical activity are performed are important variables for this protection. It is important to understand precisely when in life physical activity begins to determine health benefits. Children born with inadequate weight seem to be at higher risk for disease in adulthood. The aim of this study was to compare in preschool children (four years) from a birth cohort of 2005 the city of Aracaju-SE adequacy of birth weight interferes with the activity level. This study is a nested case-control in this cohort and had a sample of 72 children, 43 Adequate for Gestational Age (AGA) and 29 Large for Gestational Age (LGA). For both groups there was no association between adequacy of birth weight and physical activity level. Significant differences were found when genders were compared (boys more active than girls). It was not possible to observe a statistically significant difference in the Body Mass Index between groups. Measurement of physical activity by accelerometer Actigraph device GT1M was considered feasible and more valid than the questionnaire. Pre-school is the age at which children are establishing habits, turning crucial for intervention aiming to incorporate physical activity into their routines. As this is an important and sensitive to intervention, more research is needed with larger samples and other age groups to study more thoroughly this relationship.